Coordinated variation in root and leaf functional traits of Hippophae rhamnoides treated at different stump heights in feldspathic sandstone areas of Inner Mongolia - Liu, Lu; Guo, Yuefeng; Liu, Xiaoyu; Yao, Yunfeng; Qi, Wei (Frontiers in Plant Science, 2023)
This study was aimed to clarify the effects of stumping on root and leaf traits as well as the tradeoffs and synergies of decaying Hippophae rhamnoides in feldspathic sandstone areas, and to select the optimal stump height that contributed to the recovery and growth of H. rhamnoides. variations and coordination between leaf traits and fine root traits of H. rhamnoides were studied at different stump heights (0, 10, 15, 20 cm, and no stumping) in feldspathic sandstone areas. All functional traits of the leaves and roots, except the leaf C content (LC) and the fine root C content (FRC), were significantly different among different stump heights. The total variation coefficient was the largest in the specific leaf area (SLA), which is therefore the most sensitive trait. Compared to non-stumping, SLA, leaf N content (LN), specific root length (SRL) and fine root N content (FRN) all improved significantly at stump height of 15 cm, but leaf tissue density (LTD), leaf dry matter content (LDMC), leaf carbon to nitrogen ratio (LC : LN), fine root tissue density (FRTD), fine root dry matter content (FRDMC) and fine root carbon to nitrogen ratio (FRC : FRN) all decreased significantly. The leaf traits of H. rhamnoides at different stump heights follow the leaf economic spectrum, and the fine roots show a similar trait syndrome to the leaves. SLA and LN are positively correlated with SRL and FRN and negatively with FRTD and FRC : FRN. LDMC and LC : LN are positively correlated with FRTD and FRC : FRN, and negatively correlated SRL and RN. The stumped H. rhamnoides changes to the ‘rapid investment–return type’ resource trade-offs strategy, and the growth rate is maximized at the stump height of 15 cm. Our findings are critical to the prevention and control of vegetation recovery and soil erosion in feldspathic sandstone areas.